E-019 Outcome of the Patients Presenting with Basilar Occlusions in a Busy Stroke Center Treated with new Generation Stent Retrievers. (29th July 2016) - Akhtar, I; Halpin, J; Holloway, W; Martin, C; Akhtar, N
Abstract : Introduction/purpose: Posterior circulation strokes with basilar occlusions have the worse clinical outcomes of all strokes. The outcome data utilizing new generation stent retrievers is sparse as most of the clinical trials evaluating stent retrievers exclude posterior circulation strokes. This retrospective review was undertaken to report our experience with stent retrievers in acute basilar occlusions. Materials/methods: From March 2012 to March 2016, we performed thrombus retrieval in 337 patients. Retrospective review revealed 23 patients (7%) with basilar occlusions were treated with stent retrieval and adjuvant therapy. Patient demographic: ○ 23 patients: 16 males, 7 females ○ Age ranged from 29–87 years (mean: 60.4, median: 63) Presentation time from symptom onset: ○ 0–3 hours: 4 patients ○ 3–8 hours: 6 patients ○ Time unknown: 13 patients. 9/13 patients: wake up strokes ○ Intravenous TPA was administered in 4/23 patients (17%) ○ Initial non contrast CT scan findings: ○ Negative: 17 patients ○ Positive for patchy strokes: 6 patients ○ Dense basilar artery on CT: 9 patients Thrombectomy device utilized: ○ Solitaire 4x20mm in 7, 4x40mm in 4, 6x30mm in 9, 6x20mm in 1 patient ○ In one patient solitaire could not be deployed ○ In one patient: Trevo was utilized ○ Balloon guide catheters were used in 10 patients with balloon dilated in the Subclavian artery. In 9 patients, local suction with stent retrievers was applied.o 6/23 patients required stent placement for underlying stenosis Results: NIHSS ○ NIHSS at presentation range from 2–38 (mean: 24, median: 22.5) ○ NIHSS 24 hour post intervention range from 0–38 (mean: 17, median: 13.5) Number of passes: ○ Pass attempts range from 1–5. Successful 1 st pass achieved in 10 patients (mean number of passes: 2/patient) TICI scores: ○ Initial TICI pre procedure: TICI 0: 19 patients, TICI 1/2a: 4 patients ○ Final TICI score post procedure: TICI 3: 11, TICI 2c: 2, TICI 2b: 5, TICI 1: 2, and TICI 0: 3 patients. Successful reperfusion (TICI 2b or higher) was achieved in 18/23 patients (78.3%). Outcome: ○ Modified Rankin Score (MRS) at discharge/90 days: Death (6): 10 patients MRS 0–2 (good clinical outcome group): 7/23 (30%) MRS 3–5: 5 patients 1 patient declined follow up Good clinical outcome group: 5/7 patients presented within 6 hours of symptom onset while 2/7 patients presented as wake up strokes. Initial CT findings were negative in all 7 patients. Conclusion: Although the successful recanalization rate (TICI 2 b or higher) in basilar occlusions is high (18/23 (78.3%)), the mortality (10/23 (43%)) and morbidity with MRS ≥ 3 (5/23 (22%)) remains disappointingly high. In our study, good clinical outcome (MRS 0–2) was achieved in 30% (7/23) of patients, better than the natural course in basilar occlusions, which is encouraging. This group highlights the value of early presentation and a negative CT as strong predictors of a good outcome. The prognosis in patients with basilar occlusions with positive CT findings and unknown time of onset remain guarded. Disclosures: I. Akhtar: None. J. Halpin: None. W. Holloway: None. C. Martin: None. N. Akhtar: None.